Pengaruh Customer Relationship Management (CRM) terhadap Customer Loyalty dengan Customer Satisfaction sebagai Variabel Intervening pada Jasa Service PT Nasmoco Siliwangi Semarang - Mayang Kurnia Widhi; Ngatno Ngatno; Naili Farida (Universitas Diponegoro, 2023)
The automotive business in Indonesia is experiencing increasingly fierce competition. The development of sales in Indonesia, which fluctuates, has made automotive entrepreneurs compete more creatively and innovatively to maintain customer loyalty. One of the automotive companies that always maintains customer loyalty is PT. Nasmoco Siliwangi. This study aims to determine the effect of Customer Relationship management on Customer Loyalty through Customer Satifaction at Nasmoco Siliwangi Semarang service. The type of research used is explanatory research with a sample size of 100 respondents who are customers of Nasmoco Siliwangi services with certain criteria. The sampling technique used is nonprobability sampling with purposive sampling method. Quantitative analysis techniques will be calculated using the Partial Least Square (PLS) method using SmartPLS 4.0 software. The results of this study indicate a significant influence of Customer Relationship management with Customer Satisfaction at Nasmoco Siliwangi Semarang in a positive direction. Customer Relationship management has a significant influence on Customer Loyalty in a positive direction. And Customer Satisfaction has a significant influence on Customer Loyalty in a positive direction. In this study, Customer Satisfaction has an indirect effect on Customer Relationship management on Customer Loyalty. The suggestion in this study is that Nasmoco Siliwangi can improve Customer Relationship management in order to create higher customer satisfaction to increase customer loyalty.Bisnis otomotif di Indonesia mengalami persaingan yang semakin ketat. Perkembangan penjualan di Indonesia yang naik turun menjadikan para pengusaha otomotif bersaing lebih kreatif dan inovatif untuk menjaga loyalitas pelanggan. Salah satu perusahaan otomotif yang selalu menjaga loyalitas pelanggan adalah PT. Nasmoco Siliwangi. Penelitian ini bertujuan untuk mengetahui pengaruh Customer Relationship management terhadap Customer Loyalty melalui Customer Satifaction pada jasa service Nasmoco Siliwangi Semarang. Tipe penelitian yang digunakan adalah explanatory research dengan jumlah sampel adalah 100 responden yang merupakan pelanggan jasa service Nasmoco Siliwangi dengan kriteria tertentu. Teknik pengambilan sampel yang digunakan adalah nonprobability sampling dengan metode pusposive sampling. Teknik analisis kuantitatif akan dihitung menggunakan metode Partial Least Square (PLS) dengan menggunakan software SmartPLS 4.0. Hasil penelitian ini menunjukkan adanya pengaruh secara signifikan dari Customer Relationship management dengan Customer Satisfaction di Nasmoco Siliwangi Semarang ke arah positif. Customer Relationship management memiliki pengaruh signifikan terhadap Customer Loyalty ke arah positif. Dan Customer Satisfaction memiliki pengaruh signifikan terhadap Customer Loyalty ke arah positif. Pada penelitian ini, Customer Satisfaction memiliki pengaruh tidak langsung pada Customer Relationship management terhadap Customer Loyalty. Saran pada penelitian ini adalah Nasmoco Siliwangi dapat meningkatkan Customer Relationship management agar menciptakan kepuasan pelanggan yang lebih tinggi untuk meningkatkan loyalitas pelanggan.